Variables, indicators and methods for the analysis of territorial cohesion: difficulties and challenges in low density areas - Hector Martinez Sanchez-Mateos; Felix Pillet Capdepon; Maria del Carmen Ca\~nizares Ruiz; Angel Raul Ruiz Pulpon; Julio Plaza Tabasco; Jesus Francisco Santos Santos (European Regional Science Association (ERSA), 2011)
Previous research carried out by this same authors went through the analysis of data sources and their potential to apply the polycentrism approach to territories where the urban features is weak (specifically in Castilla-La Mancha, Spain). Lately, several hubs were identified as potential centres and sub-centres in a regional articulation, helping out to delimitate accurately the map of polycentrism and Functional Urban Areas (FUAs) for each of them. Currently, we hope to depict those FUAs, highlighting the spatial cohesion, and looking for a better geographical knowledge, in accordance with current European standards. The most common methods to characterize functional areas used to be linked with numerous variables, demographic and economic, usually available and updated. Nevertheless, to go deepen is a difficult task because the broad range of indicators involved and the outcomes of recent dynamics. The specific aim of this paper is reviewing methodologies and datasets sources frequently used in the spatial evaluation, stressing those which focus less populated or dispersed areas. The analysis is driven by the difficulty to effectively assess what spatial cohesion is and how can it be measured, especially in these zones where this concept is crucial to understand the regional development.
Keywords: 330